1987
DOI: 10.1128/aem.53.4.621-626.1987
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of virucidal agents in activated sludge

Abstract: A comprehensive study was carried out to determine the properties of agents responsible for loss of virus infectivity in mixed-liquor suspended solids (MLSS) of activated sludge. Initial experiments revealed that model enteric viruses (poliovirus-1 and rotavirus SA-li) were irreversibly inactivated in MLSS and released their RNA genomes. Enteric viruses belonging to other genera (echovirus-12, coxsackievirus A13, reovirus-3) were also shown to lose infectivity in MLSS. Although the virucidal activity decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
2
6
2
Order By: Relevance
“…This finding suggests the possibility that the antiviral activity observed in aquatic ecosystems may be due to the production of low-molecular-weight substances. The antiviral substance 46NW-04A described in this report was different from the proteolytic enzymes described by Ward et al (1986) and Knowlton and Ward (1987) because 46NW-04A has a molecular weight of 1,126. Negative ninhydrin reaction suggested that 46NW-04A was a peptide blocked in its N-terminal residues.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This finding suggests the possibility that the antiviral activity observed in aquatic ecosystems may be due to the production of low-molecular-weight substances. The antiviral substance 46NW-04A described in this report was different from the proteolytic enzymes described by Ward et al (1986) and Knowlton and Ward (1987) because 46NW-04A has a molecular weight of 1,126. Negative ninhydrin reaction suggested that 46NW-04A was a peptide blocked in its N-terminal residues.…”
Section: Discussioncontrasting
confidence: 64%
“…However, there have been no reports on antiviral substances actually isolated and characterized from microorganisms indigenous to aquatic environments. Several investigators have suggested that the causative agent of viral inactivation was proteolytic bacterial enzymes (Toranzo et al 1982(Toranzo et al , 1983Ward et al 1986;Knowlton and Ward 1987), but few compounds with antiviral action have been isolated from microorganisms in aquatic environments. Most reports are limited to antibiotics active against bacteria or fungi (Rosenfeld and Zobell 1947;Grein and Meyers 1958;Burkholder et al 1966;Doggett 1968;Ballester et al 1977;Wratten et al 1977;Lemos et al 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the water content of sludge can be an important parameter, as it determines the mobility and concentration of inactivating or protective agents, and water evaporation itself can lead to virus inactivation during the dewatering process (90)(91)(92). Finally, microbial or related enzyme activity may also enhance inactivation during sludge digestion (93)(94)(95)(96).…”
Section: Discussionmentioning
confidence: 99%
“…The viruses tested here can be grouped into thermolabile viruses that are comparatively chemoresistant (rotaviruses, enteroviruses) and thermostable viruses that are chemolabile (parvoviruses). In this connection chemoresistance means that viruses are relatively insensitive to chemical factors such as ammonia and detergents (19)(20)(21) or to microbial factors (10) present in the sludge.…”
Section: Discussionmentioning
confidence: 99%